Active learning in high school students' leisure time - Amarin Tawata (2018)
© Common Ground, Amarin Tawata, Pitipong Yodmongkol, Nopasit Chakpitak, Pradon Sureephong. Adolescents' leisure time may involve risky behaviors and entertainment activities that interrupt learning. Presently, learning environments surround adolescents in their daily lives, and they have opportunities to be active learners during their leisure time. However, studies about active learning have mainly focused on learning activities in classrooms and assessed outcomes of studying. This study investigates how active learning affects high school students' use of their leisure time. The study compared students' leisure time activities through a pretest, ongoing test and posttest. The results showed that students' activities can be divided into conventional and ICT activities. All ICT activities were affected by active learning. The number of students who used the Internet for learning steadily increased with statistical significance. Additionally, the number of students who used social networking sites for interaction with peers and teachers for learning increased with statistical significant.